The South African community pharmacist and Type 2 Diabetes Mellitus a pharmaceutical care intervention - Hill, Peter William (Rhodes University, Faculty of Pharmacy, Pharmacy, 2009)
Type 2 diabetes mellitus is a chronic disease of pandemic magnitude, increasingly contributing to the disease burden of countries in the developing world, largely because of the effects of unhealthy lifestyles fuelled by unbridled urbanisation. In certain settings, patients with diabetes are more likely to have a healthcare encounter with a pharmacist than with any other healthcare provider. The overall aim of the study was to investigate the potential of South African community pharmacists to positively influence patient adherence and metabolic control in Type 2 diabetes. The designated primary endpoint was glycated haemoglobin, with the intermediate health outcomes of blood lipids, serum creatinine, blood pressure and body mass index serving as secondary endpoints. Community pharmacists and their associated Type 2 diabetes patients were recruited from areas throughout South Africa using the communication media of various nonstatutory pharmacy organisations. Although 156 pharmacists initially indicated interest in participating in the study, only 28 pharmacists and 153 patients were enrolled prior to baseline data collection. Of these, 16 pharmacists and 57 patients participated in the study for the full twelve months. Baseline clinical and psychosocial data were collected, after which pharmacists and their patients were randomised, nine pharmacists and 34 patients to the intervention group and 8 pharmacists and 27 patients to the control group. The sample size calculation revealed that each group required the participation of a minimum of 35 patients. Control pharmacists were requested to offer standard pharmaceutical care, while the intervention pharmacists were provided with a scope of practice diabetes care plan to guide the diabetes care they were to provide. Data were again collected 12-months postbaseline. At baseline, proportionally more intervention patients (82.4%) than control patients (59.3%) were using only oral anti-diabetes agents (i.e. not in combination with insulin), while insulin usage, either alone or in combination with oral agents was conversely greater in the control group (40.7%) than in the intervention group (17.6%) (Chi-squared test, p=0.013). Approximately half of the patients (53.8% control and 47.1% intervention) reported having their HbA1c levels measured in terms of accepted guidelines. There was no significant difference in HbA1c between the groups at the end of the study (Independent t-test, p=0.514). In the control group, the mean HbA1c increased from 7.3±1.2% to 7.6±1.5%, while for the intervention patients the variable remained almost constant (8.2±2.0% at baseline and 8.2±1.8% at post-baseline). Similarly, there were no significant differences between the groups with regard to any of the designated secondary clinical endpoints. Adherence to medication and self-management recommendations was similarly good for both groups. There were no significant differences between the two groups for any of the other psychosocial variables measured. In conclusion, intervention pharmacists were not able to significantly influence glycaemic control or therapeutic adherence compared to the control pharmacists.
Keywords: Pharmacist and patient -- South Africa; Pharmaceutical services -- Patients; Pharmaceutical services -- South Africa; Pharmacists -- South Africa; Diabetes -- Treatment -- South Africa; Community health services -- South Africa